Komunikasi Visual Iklan Cetak Rokok di Indonesia Kurun Waktu 1950 -2000 - Rama Kertamukti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2010)
Visual Communication activities in 1950-2000 actual cigarette Advertisement in packaging his message began to flourish in the late 90s with the beginning of the modern trends with ad visualization further highlight the ability to package the message in a way that “new”, the Advertisement contains a more interesting originality out of the path message vulgarly without the superior power of creativity is only repeating the old ways of communicating visually compared with 50s. Advertising is a message that offers products intended to the public through a media and advertising is the biggest benefit of bringing the message to be conveyed by the producer to the general public. Sometimes Visual Communication submitted by the Advertisement in the plot that makes the society to behave in a consumptive. Advertising is the tip of the spear, in this case is one of the important parts in the process of achieving success of a program to disseminate, in other words visual communication plays in achieving the goals producer or the sender’s main message.